Sulfur-Containing Monoterpenoids as Potential Antithrombotic Drugs: Research in the Molecular Mechanism of Coagulation Activity Using Pinanyl Sulfoxide as an Example - Nikitina, Liliya E.; Kiselev, Sergei V.; Startseva, Valeriya A.; Bodrov, Andrei V.; Azizova, Zulfiya R.; Shipina, Olga T.; Fedyunina, Inna V.; Boichuk, Sergei V.; Lodochnikova, Olga A.; Klochkov, Vladimir V.; Galiullina, Leisan F.; Khaliullina, Aliya V. (Frontiers in Pharmacology, 2018)
In this article we present the synthesis of enantiomerically pure sulfoxide and study the influence of this compound on hemostasis. Detailed NMR studies and molecular dynamics simulations using sodium dodecyl sulfate (SDS) membrane models indicated that the bicyclic fragment of sulfoxide was embedded into the SDS micelle whereas the -SO(CH2)2OH fragment remained on the surface of the micelle and was in contact with the solvent. We also found that the pro-coagulative activity of sulfoxide was due to its ability to inhibit platelet activation and inhibited the catalytic activity of phospholipid surface which was involved in formation of coagulation clotting factor complexes.